2013
DOI: 10.1136/annrheumdis-2013-eular.3159
|View full text |Cite
|
Sign up to set email alerts
|

AB0837-HPR Core stability exercises: in water or on land? comparison of the effects of two different core stabilization trainings

Abstract: Background Core stabilization exercises have a theoretical basis and are used in the treatment of low back pain. But the effects of core stability exercises performed in water are unknown. Objectives To determine and compare the effects of Core stability exercise programs performed in different environments in low back pain (LBP) patients. Methods Twenty-three patients (47.78±13.20 years) and fifteen age-sex matched healthy controls (46.67±13.69) were included to the study. Patients were randomly divided int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…The water-based group demonstrated greater improvement in these two measures compared with the land group (F 2 ) ( Table 2). Similar to the results of the present study, some other studies also revealed the effectiveness of exercising in water [12,17,20], in contradiction to others that found no difference between land-based and water-based exercise [18,19,28].…”
Section: Resultssupporting
confidence: 74%
See 2 more Smart Citations
“…The water-based group demonstrated greater improvement in these two measures compared with the land group (F 2 ) ( Table 2). Similar to the results of the present study, some other studies also revealed the effectiveness of exercising in water [12,17,20], in contradiction to others that found no difference between land-based and water-based exercise [18,19,28].…”
Section: Resultssupporting
confidence: 74%
“…Two other studies were published comparing the effect of stability exercise in water and on land for LBP patients. However, no difference was found in these studies between the water program and land program [19,29]. Earlier studies from the 1980s and 1990s reported positive effect of water exercise [30,31].…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation